Evaluation of Giomer Using Eighth Generation Bonding Agent and Resin-Modified Glass Ionomer Cement Restoration in Non-Carious Cervical Lesions - Rajvi Bheda; Sanjyot Mulay; Anita Sanap Tandale (Indian Journal of Dental Research)
Introduction: Non-carious cervical lesions (NCCL) raise a considerable restorative challenge for the dentist in bonding, as adhesion is not as strong and predictable as enamel bonding. A critical factor for restorative success is the selection of restorative material. Clinicians have tried many restorative materials and techniques to obtain the best performance. The aim of the present study was to evaluate and compare the clinical outcome of a Giomer and Resin modified glass ionomer cement (RMGIC) restoration in NCCL using united states public health service (USPHS) criteria at baseline, 3, 6 and 12 months. Materials and Method: Patients from age 25 - 50 years having non-carious cervical lesions on both the sides and requiring restorations were screened. 20 patients were selected and further divided into 2 groups using simple random sampling technique. Group A- Beautifil II restoration using G-Premio bond (n = 10) and Group B- Ketac N100 restoration (n = 10). Restorations were done according to manufacturer's instructions and consequently evaluated at baseline, 3, 6 and 12 months using the USPHS criteria for marginal discolouration, marginal integrity, surface texture, colour match, gross fracture and post-operative sensitivity. Results: Giomer restorations showed better results than RMGIC. There was decrease in alpha ratings in both the study groups i.e., Giomer and RMGIC from 6 to 12 months. Discussion: The overall findings suggest that both Giomer and RMGIC gave satisfactory clinical results when used to restore non-carious cervical lesions. Both the materials can successfully be used since there was no statistically significant difference in the clinical outcome.